2018
DOI: 10.1039/c7nr08545a
|View full text |Cite
|
Sign up to set email alerts
|

The stability limits of highly active nitrogen doped carbon ORR nano-catalysts: a mechanistic study of degradation reactions

Abstract: A new approach in electrode catalysis bearing immense potential for electrochemical technologies is the prospect of carbon-based electrodes. Pristine carbon nanostructures are relatively inert and modifications like nitrogen doping are known for their beneficial effects on the electrochemical activity of carbon nanomaterials in both alkaline and acidic media. However, the long-term stability of these materials, especially in an acidic environment, is rarely mentioned. Here, we evaluate the stability and long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Despite the low amount of pyridinic N present initially after the N-doping process, the diminished pyridinic N could also be linked to the favorable degradation of this N species in the form of NH 3 after recombination with NH 2 through the diffusion during the cysteamine functionalization. 47 It has been reported that the control of the type of N species formed in the doped graphene network plays a very important role in affecting the electrochemical behavior of supercapacitors. 48,49 From the previous studies, pyrrolic N is found to increase the wettability of graphene in aqueous electrolytes besides its enhanced contribution to pseudocapacitance.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the low amount of pyridinic N present initially after the N-doping process, the diminished pyridinic N could also be linked to the favorable degradation of this N species in the form of NH 3 after recombination with NH 2 through the diffusion during the cysteamine functionalization. 47 It has been reported that the control of the type of N species formed in the doped graphene network plays a very important role in affecting the electrochemical behavior of supercapacitors. 48,49 From the previous studies, pyrrolic N is found to increase the wettability of graphene in aqueous electrolytes besides its enhanced contribution to pseudocapacitance.…”
Section: Resultsmentioning
confidence: 99%
“…The structures with low or very high surface area (600 g −1 < and 1500 g −1 >) have showed poor activity (Figure c), meaning that the stable active sites and defects have to be introduced to their surfaces for improving the electrocatalytic activity and the stability. The fact that pyridinic N site protonates in acid to form pyrrolic‐N sites could be one reason for the poor activity and stability, meaning that N composition before and after ORR has to be determined with advanced analytical tools and compared . The other reason for low electrocatalytic performance in acid could be due to the adsorption of sulfate anions on the active sites.…”
Section: D Carbons For the Orrmentioning
confidence: 99%
“…The fact that pyridinic N site protonates in acid to form pyrrolic-N sites could be one reason for the poor activity and stability, meaning that N composition before and after ORR has to be determined with advanced analytical tools and compared. [228,229] The other reason for low electrocatalytic performance in acid could be due to the adsorption of sulfate anions on the active sites.…”
Section: Single Element-doped 3d Carbonsmentioning
confidence: 99%
“…Solid acids are an alternative and interesting class of proton conducting electrolytes for fuel cell applications. After Haile [1][2][3][4] demonstrated the general concept employing CsH 2 PO 4 (CDP) in solid acid-based fuel cells (SAFCs) they were further developed by a number of researchers [1,3,[5][6][7][8][9][10][11][12][13][14][15] and appreciated for their intermediate operating temperature (230-260 • C) in comparison to polymer electrolyte membranes fuel cells (PEMFCs). Although, SAFCs feature a number of advantages the use of solid acids for fuel cell electrolytes poses at least two major obstacles for their large-scale commercialization.…”
Section: Introductionmentioning
confidence: 99%